Autophagy-Related Long Non-coding RNA Is a Prognostic Indicator for Bladder Cancer - Wan, Jiaming; Guo, Cheng; Fang, Hongpeng; Xu, Zhongye; Hu, Yongwei; Luo, Yun (Frontiers in Oncology, 2021)
Bladder cancer (BC) is one of the most common malignant urinary system tumors, and has a poor prognosis. In recent years, autophagy has been closely linked to the development of BC. Therefore, we investigated the potential prognostic role of autophagy-related long noncoding RNA (lncRNA) in patients with BC. We obtained lncRNA information from the Cancer Genome Atlas (TCGA) dataset and autophagy genes from the human autophagy database and performed co-expression analysis to identify lncRNAs associated with autophagy genes. Then, we divided the data into training and testing groups. In the training group, 15 autophagy-related lncRNAs were found to have prognostic value (AC026369.3, USP30-as1, AC007991.2, AC104785.1, AC010503.4, AC037198.1, AC010331.1, AF131215.6, AC084357.2, THUMPD3-AS1, U62317.4, MAN1B1-DTt, AC024060.1, AL662844.4, and AC005229.4). The patients were divided into low- and high-risk groups based on the prognostic lncRNAs. Overall survival time was shorter for the high-risk group than it was for the low-risk group [risk ratio (HR) = 1.08, 95% CI: 1.06–1.10; P < 0.0001]. Using our model, the defined risk value can predict patient prognosis. Next, the model was assessed in the TCGA testing group to further validate these results. A total of 203 patients with BC were recruited to verify the lncRNA characteristics. We divided these patients into high- and low-risk groups. Testing data set results show that the survival time of is shorter in high-risk patients than in low-risk patients. In the training group, the area under the curve was greater than 0.7, indicating a high level of accuracy. The area under the curve for the risk model was greater than that for each clinical feature alone, indicating that the risk value of the model was the best indicator for predicting prognosis. Further training data analysis showed that the gene set was significantly enriched in cancer related pathways, including actin cytoskeleton regulation and gap junctions. In conclusion, our 15 autophagy-related lncRNAs have prognostic potential for BC, and may play key roles in BC biology.